Temporal and Spatial Stability on the Population Structure of Consumed and Illegally Traded Big-Headed Amazon River Turtle in the Negro River Basin, Central Amazon, Brazil - Pezzuti, Juarez C. B.; Oliveira, Tamires; Pantoja-Lima, Jackson; Rebêlo, George Henrique; Félix-Silva, Daniely (Frontiers in Ecology and Evolution, 2022)
Fresh water turtles are a valuable food resource for riverine communities. Freshwater turtles have been historically overharvested thorough all major tropical large river basins, with consequent gradual population decrease. Even species accounted to be incredibly abundant are declining, and in many cases were brought to a condition of nearly extinction. The collection of adult females during breeding season on nesting beaches is considered a major factor in population decline and subsequent loss of food source. There is growing consensus that adult females constitute the category which turtle populations can least afford to lose. In the Negro River Basin, the Podocnemidid Big-Headed Amazon river turtle, Peltocephalus dumerilianus, is heavily exploited for consumption and poached for illegal trade among riverine communities and cities. Between 1997-2002 and in 2019, we measured live turtles and carapaces of Big-Headed turtles in the city of Barcelos and surroundings, and among the riverine families living in the Jaú National Park. We compared animal sizes and sex ratios between areas, periods, and between consumed and traded individuals. We found no differences between areas, even those close to Barcelos and the ones belonging to remote areas where pressure levels are expressively lower. The individuals consumed in Jaú National Park are larger than those poached for the illegal trade in both areas. There was an increase in average size between the two periods considered. Sex ratio was slightly skewed toward males, which were larger, and did not differ between areas and periods. We suggest that the Big-Headed populations can support current extraction levels, and that this apparent sustainability is related to the absence of adult female capture during nesting for this species. We recommend protection strategies for other Amazon Podocnemidid species that focus on the protection of nesting beaches and surrounding areas where adults occupy, specifically in areas under communal protection.